Regulation of TLR10 Expression and Its Role in Chemotaxis of Human Neutrophils - Yadu Balachandran; Sarah Caldwell; Gurpreet Kaur Aulakh; Baljit Singh (Karger Publishers, 2022)
Toll-like receptors are innate immune receptors that play a critical role in pathogen-associated molecular pattern recognition. TLR10 was recently identified and very limited data are available on its expression, mechanisms that regulate its expression, and its role in primary immune cells. To study the expression pattern of TLR10 in primary immune cells, we examined TLR10 protein expression in naive and Escherichia coli lipopolysaccharide (LPS)-activated human neutrophils. Human neutrophils challenged with LPS showed a decrease in total and surface TLR10 expression at 90 min. TLR10 in LPS-activated neutrophils colocalized with flotallin-1, a lipid raft marker, and EEA-1, an early endosomal marker, to suggest its endocytosis. There was increased colocalization of TLR10 with TLR4 at LPS 60 min followed by decrease at later LPS treatment times. Treatment with TLR4 neutralizing antibody decreased cytoplasmic localization of TLR10 in LPS-treated neutrophils. Reactive oxygen species (ROS) depletion and neutralization of p65 subunit of NF-κB in LPS-treated neutrophils decreased TLR10 expression. Live cell imaging of LPS-activated neutrophils showed TLR10 translocation in the leading edge and TLR10 knockdown in neutrophils reduced their fMLP-induced chemotaxis and the number of neutrophils with pseudopodia but without affecting the expression of key proteins of actin nucleation process, ARP-3 and Diap1. Taken together, our findings show that neutrophil activation alters TLR10 expression through ROS production and NF-κB regulation, and TLR10 knockdown reduced neutrophil chemotaxis.